2019
DOI: 10.1002/jso.25721
|View full text |Cite
|
Sign up to set email alerts
|

The role of preoperative albumin‐bilirubin grade for oncological risk stratification in liver transplant patients with hepatocellular carcinoma

Abstract: Background and Objectives: Albumin-bilirubin (ALBI) score was shown to correlate with liver function and tumor recurrence after hepatectomy for hepatocellular carcinoma (HCC). The aim of this study was to assess the prognostic value of ALBI grade in liver transplantation (LT) patients with HCC.Methods: Pre-LT available independent predictors of recurrence-free survival (RFS) and microvascular tumor invasion (MVI) were determined in 123 patients with HCC.Results: Posttransplant HCC recurrence rates were 10.5%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
1
18
1
Order By: Relevance
“…Interestingly, patients with a CRP of ≥1 mg/mL independent of Milan were associated with an inferior oncological outcome [17]. A cumulative HCC recurrence risk according to a novel oncological risk score (ORS) including AFP, CRP, and ALBI grade was demonstrated [15, 39]. Thus, ALBI grade seems to be of value for better preoperative oncological risk stratification to calculate the novel ORS.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, patients with a CRP of ≥1 mg/mL independent of Milan were associated with an inferior oncological outcome [17]. A cumulative HCC recurrence risk according to a novel oncological risk score (ORS) including AFP, CRP, and ALBI grade was demonstrated [15, 39]. Thus, ALBI grade seems to be of value for better preoperative oncological risk stratification to calculate the novel ORS.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that postoperative complications were related to preoperative clinical markers, including albumin, total bilirubin and ALBI scores [ 37 , 38 ]. The ALBI score was found to play an important role in evaluating the functional performance of the liver [ 39 , 40 ]. A poor grade (ALBI grade 3) was significantly associated with postoperative complications and mortality during hospitalization [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another report, ALBI grade 2 (HR = 1.827, p < 0.001) and grade 3 (HR 2.589, p < 0.001) were shown to be independent risk factors of poor survival in patients with HCC within the Milan criteria (single tumor less than 5 cm in size or no more than three tumors, all less than 3 cm in diameter) [20] and treated with liver transplantation [21], while an ALBI-based prognostic model with a total range of 0 to 6 points was derived based on the sum of five variables; 1 point each for age ≥65 years, alpha-fetoprotein (AFP) >100 ng/mL, presence of ascites, performance status 1 to 4, and ALBI grade 2, with 2 points for ALBI grade 3 [21]. Kormberg et al reported that post-transplant recurrence rates for patients classified as ALBI grade 1, 2, and 3 were 10.5%, 15.9%, and 68.2%, respectively (p < 0.01) [22]. In addition, the ALBI grade might have a good value for predicting post-transplant complications.…”
Section: Liver Transplantationmentioning
confidence: 99%